2015
DOI: 10.1177/1367006914564566
|View full text |Cite
|
Sign up to set email alerts
|

Stop consonant production of French immersion students in Western Canada: A study of voice onset time

Abstract: Objectives/research questions: The present study investigates the development of French stop consonants among English-speaking children who are enrolled in an early French immersion program in Lethbridge, Alberta, Canada. Our goal is to observe the stop consonant production pattern, and to determine whether interactions between the two language systems occur, while examining student progression with increasing experience. Methodology: Fifty-six students in grades 1, 3, and 5 participated in a speech production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the area of phonological acquisition, one of the most extensive explorations is the acquisition of VOT; Kehoe et al (2004), for example, measured the VOT production of word-initial stop consonants of German by four German-Spanish bilingual children and compared them to the three monolingual German peers using naturalistic speech recordings. Similarly, Fabiano- Smith and Goldstein (2010) Departing from the different patterns of VOT in the two languages, children in these previous studies were found to demonstrate the followings: in the German-English data, they indicated (1) delay in the phonetic realization of voicing, (2) transfer of voicing features, and (3) no cross-language influence in the phonetic realization (Kehoe et al, 2004), in the Spanish-English, (1) monolingual and bilingual children generally differed on VOT in English, but not in Spanish and (2) no statistically significant differences were found between the Spanish and the English VOT of the bilingual children, but the VOT values did differ significantly for monolingual Spanish-versus monolingual English-speaking participants (Fabiano- Smith & Goldstein, 2010), whereas in the French-English data, (1) for the French voiceless stops, French immersion students display nonnative-like VOT values in the intermediate range between monolingual English voiced and voiceless stops, (2) their English voiceless stops exhibit higher VOT values than the monolinguals' and are separate from those of their French, (3) for voiced stops, their English and French are indistinguishable, located within the range of voiced stops for monolingual English speakers (Netelenbos et al, 2015). These findings have provided important insights into how cross-linguistic interaction takes place during the acquisition of nonnative language VOTs.…”
Section: Introductionmentioning
confidence: 88%
“…In the area of phonological acquisition, one of the most extensive explorations is the acquisition of VOT; Kehoe et al (2004), for example, measured the VOT production of word-initial stop consonants of German by four German-Spanish bilingual children and compared them to the three monolingual German peers using naturalistic speech recordings. Similarly, Fabiano- Smith and Goldstein (2010) Departing from the different patterns of VOT in the two languages, children in these previous studies were found to demonstrate the followings: in the German-English data, they indicated (1) delay in the phonetic realization of voicing, (2) transfer of voicing features, and (3) no cross-language influence in the phonetic realization (Kehoe et al, 2004), in the Spanish-English, (1) monolingual and bilingual children generally differed on VOT in English, but not in Spanish and (2) no statistically significant differences were found between the Spanish and the English VOT of the bilingual children, but the VOT values did differ significantly for monolingual Spanish-versus monolingual English-speaking participants (Fabiano- Smith & Goldstein, 2010), whereas in the French-English data, (1) for the French voiceless stops, French immersion students display nonnative-like VOT values in the intermediate range between monolingual English voiced and voiceless stops, (2) their English voiceless stops exhibit higher VOT values than the monolinguals' and are separate from those of their French, (3) for voiced stops, their English and French are indistinguishable, located within the range of voiced stops for monolingual English speakers (Netelenbos et al, 2015). These findings have provided important insights into how cross-linguistic interaction takes place during the acquisition of nonnative language VOTs.…”
Section: Introductionmentioning
confidence: 88%
“…Nonetheless, English speakers whose L1 is also an aspirating language could exhibit more variable performances in learning L2 prevoiced stops. Netelenbos et al (2016) found that despite an increase in immersion learning experience, the acquisition of French initial prevoiced stops was still challenging for English-speaking children, insofar as their mean VOT was 8.9 ms. Likewise, an overall lack of prevoicing in Spanish initial voiced stops was reported by Zampini (1998), who investigated the production of Spanish initial stops by English learners.…”
Section: Discussionmentioning
confidence: 97%
“…For the IPA comparison method, one of the problems it has to deal with is that IPA can be used both as broad or narrow transcriptions that may differ in some scenarios, e.g. the phonetic realization of English word initial stop contrasts /b d g/ vs. /p t k/ could be narrowly transcribed as [p t k] vs. [p h t h k h ] (Beckman et al, 2013; Netelenbos et al, 2016). The choice of broad or narrow transcriptions in IPA can render disagreement in predicting similarity, which can cause uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations